Sears list of subject headings. - Sears, Minnie Earl, 1873-1933.; Reyes, Caroline; Rovira, Carmen (New York : Wilson, 1986)
Contains a list of subject headings to meet the needs of smaller libraries.
Bibliography: p. xxxi-xxxiii.
Professional.
Professional
Keywords: Subject headings; Subject headings